Personality traits predict dietary habits in middle-to-older adults. Issue 3 (15th March 2020) - Weston, Sara J.; Edmonds, Grant W.; Hill, Patrick L.
ABSTRACT: Personality traits are consistently associated with health behaviors, but little research has examined the role of personality on eating habits among middle-to-older adults. The current study (n = 665) examined the associations between traits and dietary habits and whether healthy eating predicted health at age 60, with the Hawaii Personality and Health Cohort. Eating healthy foods was associated with higher agreeableness, conscientiousness, emotional stability, and openness, and predicted better self-rated health and lower BMI. Eating unhealthy foods was associated with lower agreeableness, conscientiousness, emotional stability, and openness, and predicted lower self-rated health. Results were not moderated by SES.